1840 engraving depicting Louis XIV of France entitled 'What makes the... - William Makepeace... (Wikimedia Commons, 1840)
Notice iconographique issue de Wikimedia Commons. Titre: 1840 engraving depicting Louis XIV of France entitled "What makes the King?" by William Makepeace Thackeray, The Paris Sketchbook. What makes the King?, William Makepeace Thackeray, The Paris Sketchbook, 1840
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie